McAll’s Cave: characterising the rock art of the Groot Winterhoek Mountains, Eastern Cape Province, South Africa - Laue, G. (Southern African Humanities, 2017)
The Groot Winterhoek Mountains northwest of Port Elizabeth contain a body of largely unexplored rock art. McAll’s Cave, one of 38 recorded sites, contains exceptionally rich and well-preserved imagery. The range of images found in this shelter is representative of the rock art of the larger area. The content of the art places it firmly within the pan-San worldview. The presence and absence of specific imagery, quantitative analysis and manner of depiction of images show that although this art zone lies almost equidistant between the Cederberg and the Maloti-Drakensberg it shares many more similarities with that of the Cederberg and Western Cape art.